Investigation of hospital-onset meticillin-resistant Staphylococcus aureus bloodstream infections at eight high-burden acute care facilities in the USA, 2016. Issue 3 (July 2020) - Ham, D.C.; See, I.; Novosad, S.; Crist, M.; Mahon, G.; Fike, L.; Spicer, K.; Talley, P.; Flinchum, A.; Kainer, M.; Kallen, A.J.; Walters, M.S.
Summary: Background: Despite large reductions from 2005 to 2012, hospital-onset meticillin-resistant Staphylococcus aureus bloodstream infections (HO MRSA BSIs) continue to be a major source of morbidity and mortality. Aim: To describe risk factors for and underlying sources of HO MRSA BSIs. Methods: This study investigated HO MRSA BSIs at eight high-burden short-stay acute care hospitals. A case was defined as first isolation of MRSA from a blood specimen collected in 2016 on or after hospital day 4 from a patient without an MRSA-positive blood culture in the preceding 2 weeks. Case demographics and risk factors were reviewed by medical record abstraction. The potential clinical source(s) of infection were determined by consensus by a clinician panel. Findings: Of the 195 eligible cases, 186 were investigated. Cases were predominantly male (63%) and the median age was 57 years (range 0–92 years). In the 2 weeks preceding BSI, 88% of cases had indwelling devices, 31% underwent a surgical procedure and 18% underwent dialysis. The most common locations of attribution were intensive care units (ICUs) (46%) and step-down units (19%). The most commonly identified non-mutually exclusive clinical sources were central venous catheters (46%), non-surgical wounds (17%), surgical site infections (16%), non-ventilator healthcare-associated pneumonia (13%) and ventilator-associated pneumonia (11%). Conclusions: Device- and procedure-related infections were common sources of HO MRSA BSIs. Prevention strategies focused on improving adherence to existing prevention bundles for device-and procedure-associated infections and on source control for ICU patients, patients with certain indwelling devices, and patients undergoing certain high-risk surgeries are being pursued to decrease the burden of HO MRSA BSIs at these facilities.